2015
DOI: 10.1007/s00392-015-0866-8
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial deformation imaging unmasks subtle left ventricular systolic dysfunction in asymptomatic and treatment-naïve HIV patients

Abstract: HIV infection itself is accompanied by subclinical systolic dysfunction, not apparent to standard echocardiography that can be unmasked though using sensitive echocardiographic techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…But later study done by Cetin et al 16 showed positive correlation between reduced CD4 count and GLS value, though there were no significant difference between different CD4 level group below and greater than 300. There was no significant differences in conventional echocardiographic parameters between HIV population and healthy population except for transmittal E velocity (P value of 0.001) which were significantly lower in the HIV group and this finding were similar to the study done by Karavidas et al 19 and Mendes et al 15 . The diastolic function abnormalities such as reduced transmitral E velocity, an increased peak of A velocity, and an increased isovolumetric relaxation time and early filling duration has been described in HIV patients with wide variability in its incidence.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…But later study done by Cetin et al 16 showed positive correlation between reduced CD4 count and GLS value, though there were no significant difference between different CD4 level group below and greater than 300. There was no significant differences in conventional echocardiographic parameters between HIV population and healthy population except for transmittal E velocity (P value of 0.001) which were significantly lower in the HIV group and this finding were similar to the study done by Karavidas et al 19 and Mendes et al 15 . The diastolic function abnormalities such as reduced transmitral E velocity, an increased peak of A velocity, and an increased isovolumetric relaxation time and early filling duration has been described in HIV patients with wide variability in its incidence.…”
Section: Discussionsupporting
confidence: 89%
“…Our study evaluate the relationship of LV function with GLS in HIV patients to baseline CD4 count, HIV viral Load, duration of HIV diagnosis, HAART therapy and HAART therapy duration showed patients with CD4 count less than 300 cell/mm 3 had significantly lower GLS value less than -18% compared with higher CD4 count. Previous study done by Onur et al 18 and Karavidas et al 19 found no relationship between CD4 T-cells and systolic strain. But later study done by Cetin et al 16 showed positive correlation between reduced CD4 count and GLS value, though there were no significant difference between different CD4 level group below and greater than 300.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Unfortunately, this study was did not account for the duration of HIV infection and heterogeneity of the population studied [16]. In contrast, all the patients in our study were previously healthy and were documented HIV seroconverters with an average of 10 months duration of infection prior to echocardiography.…”
Section: Discussionmentioning
confidence: 94%